Evaluasi Efikasi Diri Dosen Universitas Brawijaya dalam Penggunaan Sistem Informasi Dosen dengan Menggunakan Technology Acceptance Model Termodifikasi - Siti Sarah Ramadhani; Yusi Tyroni Mursityo; Mochamad Chandra Saputra (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Lecturer Information System (SIADO) is a web-based information system that aims to facilitate lecturers in staffing administration. Some of the lecturers are still not maximizing SIADO so evaluation is needed to determine the level of acceptance of the system with a modified Technology Acceptance Model (TAM) on the variables of computer self-efficacy, attitude toward using and university support. The study used quantitative-descriptive method with an instrument in the form of a questionnaire. The population was taken as many as 2192 active lecturers in Brawijaya University with a total sample of 96 people which calculated by Slovin equation. The result was categorized in order to determine the level of dominance of each variable by calculating the total score of the respondents' answers divided by the maximum total score, the result times 100% obtained the results of five categories, namely, very low, low, medium, high and very high. The results showed that the university support (71.9%), computer self-efficacy (71%) and attitude toward using (73%) were classified into the high category. Recommendations include: improving the lecturers's experience of SIADO, creating a model for self-lecturers and improving social persuasive in the lecturer environment such as organizing SIADO operation training, improving web security, reducing functions or features that are not related to lecturer's tasks, maintaining a simple interface in order for users to always feel ease and the university can give appreciation or reward to users who have high intensity of SIADO usage.